Analisis Dampak Kebijakan Pemerintah Tentang Pemindahan Ibu Kota Terhadap Berjalannya Pemerintahan - C, Chatrine; Triadi, Irwan (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The relocation of the capital city is a strategic decision that can have significant impacts on the government's organizational structure and the management of national assets. This article aims to analyze the effects of capital relocation on the government's organizational structure and the management of national assets using a normative juridical approach and data collection through literature review. Through the analysis of various regulations, legal documents, and relevant theories, this article presents how capital relocation can affect the government's organizational structure. Additionally, the article also highlights aspects of national asset management related to capital relocation, such as the transfer of ownership and the management of infrastructure. Thus, this article contributes to the legal and administrative implications of capital relocation.